Investigating a Case of Recurrent Pleural Effusion - Patrícia Rodrigues; Maria Neves; João Pedro Ferreira; Miguel Araújo Abreu; Fernanda Almeida (Case Reports in Pulmonology)
We describe the case of a patient with long-standing Parkinson's disease and recurrent bilateral pleural effusions. The pleural fluid was an exudate, rich in normal lymphocytes, and the echocardiogram, chest computerized axial tomography, and immunological, microbiological and cytological studies were negative. The patient had been taking bromocriptine, which can be related to chronic pleural effusions. Using Pubmed, we found about 40 cases of pleuropulmonary changes or constrictive pericarditis that were related to bromocriptine. We decided to suspend this drug, with resolution of the pleural effusion and respiratory complaints for more than a year now. We discuss possible underlining mechanisms for this and emphasize the importance of collecting the past medical history and medication and of considering possible iatrogenic effects.